New theorems concerning „almost sure“ properties of realizations of Gaussian random processes - Alekseev, V. G. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Г. Алексеев. Новые теоремы о свойствах «почти наверное» реализаций гауссовских случайных процессов V. G. Alekseev. Naujos teoremos apie Gauso atsitiktinių procesų realizacijų su tikimybe 1 turimas savybes